Assessing attitude towards biology and Achievement in cell division among rural Secondary school students - Avianna Jowinis; Nyet Moi Siew (Global Academic Excellence, 2024)
Understanding cell division in Biology subject is often a challenge for students. The aim of this study was to evaluate rural secondary school students' attitudes toward biology and their achievement in cell division. A total of 249 science students from rural secondary schools participated in the study, which used the cell division test, and biology attitude questionnaire to collect data. The quantitative results showed a slight but significant relationship between students' achievement in cell division and their attitudes toward biology. The results showed a statistically significant but weak correlation between these two variables (r = .398, p < .001). The results can guide the development of pedagogical strategies that promote positive attitudes toward biology and ultimately improve student achievement in cell division in science education.